PENGARUH PENERIMAAN TUNJANGAN PROFESI, MOTIVASI KERJA, DAN PENGALAMAN MENGAJAR TERHADAP KINERJA GURU TK DI KECAMATAN KEBUMEN (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
Influence Admissions Professional Allowance, Work Motivation, Teaching Experience on Performance Kindergarten Teacher in District Kebumen Academic Year 2013/2014. This study aims to determine the effect of acceptance allowance, work motivation and teaching experience jointly or individually the kindergarten teacher performance as the District Kebumen. This research was conducted in the District Kebumen. The study population was akindergarten teacher in District Kebumen, totaling 77 people. The sampling technique used is proportional random sampling. Data collection techniques using questionnaires and data analysis techniques using multiple regression analysis and partial correlation. The results indicated a significant positive influence acceptance allowance, work motivation and teaching experience together and individually on teacher performance. It can be explained that if the variable allowance receipts, work motivation and teaching experience have increased the variable performance of teachers will also increase. There was a significant positive influence reception allowance on teacher performance. It can be explained that if the reception allowance increases, the performance of teachers will increase. There is a very significant positive effect on the performance of teachers' work motivation. It can be explained that if the work motivation of teachers has increased, then the performance will increase. There is a very significant positive effect of teaching experience on teacher performance. It can be explained that if the teaching experience of teachers is increasing the performance of teachers will be increased.